Managing Acute Lung Edema During Hyperglycemic Crises: Prioritizing Fluid Reduction or Blood Sugar Control in Non-Specialist Settings - Ardiansyah, Ryan; Putra, I Gusti Agung Gde Wilaja; Atmapraja, Lalu M Satrial Iip Widya (Cardiovascular and Cardiometabolic Journal (CCJ), 2025)
Background: Emergency admissions acute lung oedema and hyperglycemic crisis still very common and challenging. Both conditions are emergencies, where delay in treatment will cause increased morbidity and mortality. This report will discuss the case of a 62-year-old woman with acute lung oedema and hyperglycemia, as well as her emergency management. Case Summary: A 62-year-old woman present with severe shortness of breath since 2 hours before admission. The patient has a history of hypertension, diabetes mellitus, and heart disease and has not recently taken medication regularly. Physical examination revealed blood pressure: 260/132 mmHg, and SpO2: 86% Room Air. Thorax examination revealed vesicular sounds +/+, wheezing +/+, and full rhonki +/+ throughout the lung fields. Laboratory examination showed a blood sugar value of 539mg/dL. Chest X-ray shows cardiomegaly and pulmonary edema. Our patient was diagnosed with Acute Lung Oedema, hyperglycemia crisis, Hypertensive emergency. Conclusion: Management of patients with hyperglycemia and acute lung oedema is carried out simultaneously by the respective recommendations given. However, the rehydration volume in this case needs to be modified and it is important to provide fluid resuscitation conservatively. Hemodynamic assessments need to be carried out to ensure adequate fluid administration so as not to cause overhydration. -- Highlights: 1. This case underscores the challenge of managing hyperglycemic crisis alongside acute lung edema, emphasizing the importance of conservative, hemodynamically guided fluid resuscitation to balance rehydration needs with pulmonary safety.